2015
DOI: 10.1105/tpc.15.00585
|View full text |Cite
|
Sign up to set email alerts
|

Plants Release Precursors of Histone Deacetylase Inhibitors to Suppress Growth of Competitors

Abstract: To secure their access to water, light, and nutrients, many plant species have developed allelopathic strategies to suppress competitors. To this end, they release into the rhizosphere phytotoxic substances that inhibit the germination and growth of neighbors. Despite the importance of allelopathy in shaping natural plant communities and for agricultural production, the underlying molecular mechanisms are largely unknown. Here, we report that allelochemicals derived from the common class of cyclic hydroxamic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
73
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 73 publications
(103 reference statements)
3
73
0
1
Order By: Relevance
“…Previous studies have reported the defense-related properties of compounds with HDI activity, which inhibits the growth of competing organisms. Venturelli et al (2015) demonstrated that plants release aminophenoxazinone compounds, such as 2-amino-3H-phenoxazin-3-one Figure 6. Increased tolerance of quint plants to salinity stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the defense-related properties of compounds with HDI activity, which inhibits the growth of competing organisms. Venturelli et al (2015) demonstrated that plants release aminophenoxazinone compounds, such as 2-amino-3H-phenoxazin-3-one Figure 6. Increased tolerance of quint plants to salinity stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…BXD hydroxamic acids possess metal ion chelating properties (Tipton and Buell 1970) that can play a role in Fe(III) uptake (Pethő 1992a, b, 1993, 2002) and Al(III) resistance by roots (Poschenrieder et al 2005). Furthermore, benzoxazolinones can interfere with auxin binding in plants (Hasegawa et al 1992; Hoshisakoda et al 1994; Venis and Watson 1978), and the products of their metabolism by soil microorganisms are suggested to play a role in allelopathy (Kato-Noguchi et al 2010; Schulz et al 2013; Venturelli et al 2015). …”
Section: Chemical Properties and Reactivity Of Bxdsmentioning
confidence: 99%
“…2 This particular class of allelochemicals derives from the cyclic hydroxamic acids DIBOA (4-dihydroxy-2H-1,4-benzoxazin-3(4H)-one) and DIMBOA (2,4-dihydroxy-7-methoxy-2H-1,4-benzoxazin-3(4H)-one), which are contained in root exudates from many grasses, among them several major crops such as wheat, rice and maize. 3,4 We were able to show that APO and AMPO have the potential to bind to histone deacetylases (HDACs), 2 an evolutionarily highly conserved class of enzymes that govern the accessibility of the DNA by removal of acetyl groups from various amino acid residues of histone proteins. Histone acetylation is a dynamic epigenetic mark that correlates with relaxed chromatin conformation, accessible DNA and transcriptional activity (Fig.…”
mentioning
confidence: 99%
“…2 Making use of the higher solubility of APO in DMSO, we have established experimental conditions that better reflect physiologically relevant conditions. This setup will not only allow improved realism in future experiments, but will also drastically reduce costs, as APO is not commercially available and needs to be custom synthesized.…”
mentioning
confidence: 99%